CURRENT STATUS OF SAMPLE REJECTION AND NURSES’ KNOWLEDGE ON SPECIMEN COLLECTION, PRESERVATION, AND TRANSPORTATION AT THE LABORATORY CENTER OF HUU NGHI GENERAL HOSPITAL NGHE AN (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the rate and causes of sample rejection and to evaluate nurses’ knowledge of specimen collection, preservation, transportation, and handover at the Laboratory Center of Huu Nghi General Hospital, Nghe An. Subjects and Methods: A cross-sectional study was conducted on hematology, biochemistry, and microbiology specimens received from January 1 to July 1, 2021. Nurses directly involved in sample collection completed a structured questionnaire to assess their knowledge. Data from specimen logs and questionnaires were analyzed using SPSS 20.0 and Excel 2010. Results: The overall sample rejection rate was approximately 4%, mainly due to administrative errors (34%) and clotted blood. Rejection rates ranged from 3% to 8% across departments, lowest in the Outpatient Department (1%) and highest in Virology–Parasitology (12.5%). Among nurses, 49% had good knowledge, 49% moderate, and 2% limited knowledge, with variations by work experience and educational level. These results indicate that enhanced training and supervision may support improved laboratory quality. Conclusions:The sample rejection rate at the Laboratory Center of Huu Nghi General Hospital was approximately 4%, primarily due to administrative errors, with some departments showing higher-than-average rates. Nurses’ knowledge of specimen collection, preservation, and transportation was mostly good or moderate, and appeared to be associated with work experience and educational background. Strengthening training and supervision of procedures may contribute to improving laboratory quality.
Keywords: Laboratory testing, sample rejection, specimen quality, hematology, biochemistry, microbiolog